2012
DOI: 10.3892/etm.2012.476
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in key DNA repair genes and risk of head and neck cancer in a Chinese population

Abstract: Abstract. Although tobacco and alcohol consumption are the major risk factors of head and neck cancer (HNC), genetic variations of genes involved in several biological pathways, such as DNA repair genes, may affect an individual's susceptibility to HNC. However, few studies have investigated the associations between polymorphisms in DNA repair genes and HNC risk in the Chinese population. Thus, we genotyped five common, non-synonymous single-nucleotide polymorphisms (SNPs) [APEX1 (Asp148Glu), XRCC1 (Arg399Gln)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…To our knowledge, there are no previous studies on the function of c.-77T>C SNP on OPSCC or overall HNSCC risk. We also found no association of XRCC1 c.839G>A and c.1196G>A SNPs with OPSCC risk, according to previous results from overall HNSCC studies (Sturgis et al 1999;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Al-Hadyan et al 2012;Yuan et al 2012). In contrast, the variant allele A of c.1196G>A SNP was associated with decreased risk (Olshan et al 2002;Kumar et al 2012;Khlifi et al 2014) and increased risk (Choudhury et al 2014) of overall HNSCC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To our knowledge, there are no previous studies on the function of c.-77T>C SNP on OPSCC or overall HNSCC risk. We also found no association of XRCC1 c.839G>A and c.1196G>A SNPs with OPSCC risk, according to previous results from overall HNSCC studies (Sturgis et al 1999;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Al-Hadyan et al 2012;Yuan et al 2012). In contrast, the variant allele A of c.1196G>A SNP was associated with decreased risk (Olshan et al 2002;Kumar et al 2012;Khlifi et al 2014) and increased risk (Choudhury et al 2014) of overall HNSCC.…”
Section: Discussionsupporting
confidence: 58%
“…The roles of the OGG1 c.977C>G (Elahi et al 2002;Zhang et al 2004;Matullo et al 2006;Görgens et al 2007;Hall et al 2007;Kumar et al 2011;Mitra et al 2011), APEX1 c.444T>G (Matullo et al 2006;Li et al 2007); XRCC1 c.-77T>C, c.580C>T (Sturgis et al 1999;Olshan et al 2002;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Kumar et al 2012), c.839G>A (Tae et al 2004;Applebaum et al 2009;Gugatschka et al 2011;Kumar et al 2012) and c.1196G>A (Sturgis et al 1999;Olshan et al 2002;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;AlHadyan et al 2012;Kumar et al 2012;Yuan et al 2012;Choudhury et al 2014;Khlifi et al 2014) SNPs in overall HNSCC risk are still controversial or unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1; according to the inclusion criteria, a total of 29 studies with full-text articles that examined the association of the XRCC1 Arg399Gln with HNC susceptibility were found (Sturgis et al, 1999;Olshan et al, 2002;Varzim et al, 2003;Tae et al, 2004;Demokan et al, 2005;Gajecka et al, 2005;Huang et al, 2005;Rydzanicz et al, 2005;Kietthubthew et al, 2006;Matullo et al, 2006;Ramachandran et al, 2006;Ho et al, 2007;Li et al, 2007;Majumder et al, 2007;Harth et al, 2008;Yang et al, 2008;Applebaum et al, 2009;Csejtei et al, 2009;Kowalski et al, 2009;Jelonek et al, 2010;Gugatschka et al, 2011;Krupa et al, 2011;Al-Hadyan et al, 2012;Kumar et al, 2012aKumar et al, , 2012bYuan et al, 2012;Dos Reis et al, 2013;Khlifi et al, 2013;Kostrzewska-Poczekaj et al, 2013). Among them, two articles (Kumar et al, 2012a(Kumar et al, , 2012b were published using the same case series; the larger sample size (Kumar et al, 2012a) was included.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Furthermore, there is no significant risk of HNSCC for XRCC1 Arg 399 Gln genotypes among non-Hispanic white populations in the USA [26], the Hungarian population [27], or Polish population [28]. Recently, a meta analysis done by Flores-Obando et al [25] [33]. Khlifi R et al, (2013) reported that only the XRCC1 Arg 399 Gln polymorphism was associated with the risk of HNC in the Tunisian population (OR = 2.04; P = 0.001) [34].…”
Section: Base Excision Repair (Ber)mentioning
confidence: 99%
“…Reports of XRCC1 polymorphism associated with HNSCC have been published across the globe. Yuan et al [25] conducted a case-control study for a total of 397 HNSCC patients and 900 cancer free controls among the Chinese population and reported that XRCC1 exon 10 codon (Arg 399 Gln) was not significantly associated with HNSCC risk (OR=0.93, 95% CI=0.76-1.13) [25]. Furthermore, there is no significant risk of HNSCC for XRCC1 Arg 399 Gln genotypes among non-Hispanic white populations in the USA [26], the Hungarian population [27], or Polish population [28].…”
Section: Base Excision Repair (Ber)mentioning
confidence: 99%